Investigação da influência do grau de cristalinidade do grafite sobre a produção de óxido de grafite visando a síntese de materiais híbridos com sílica - Vieira, Mariana Arpini (2015)
In the present work we investigate the influence of the degree of crystallinity of graphite on the production of graphite oxide (GO). Graphite precursors with varying degrees of crystallinity and structural defects were produced by milling a high purity graphite rod during different times and the milled materials were used for the synthesis of GO, using a modified Hummers method. The products were characterized by X-ray diffraction (XRD), thermogravimetry, solid-state 13C nuclear magnetic resonance (NMR), elemental and textural analysis and ultraviolet–visible absorption spectrophotometry. 13C NMR spectra revealed the presence of epoxy, hydroxyl, carbonyl and lactol groups in the oxides. The oxidation degree was found to be largely dependent on the milling time,with the best GO samples being produced from graphites with intermediate milling times. These results were rationalized in terms of the structural changes brought about by the milling process, as revealed by the solid-state 13C NMR spectra and the XRD patterns obtained for the milled graphites. Then, a silica-OG hybrid was synthesized from the GO obtained from a milled graphite with 30 min of milling time. The silica-GO hybrid was characterized by XRD, TG and solid-state 13C and 29Si NMR. The results evidenced the presence of nanostructured or amorphous silica in the hybrid and suggested the interaction of silica particles with the oxide by hydrogen bonds formed between the silicate groups and the oxygen functionalities present in the GO.